PENILAIAN RISIKO KECELAKAAN KERJA PADA PENGOPERASIAN CC (CONTAINER CRANE) DI PT X SURABAYA - Nyco Nugroho (Universitas Airlangga, 2016)
The operation of CC has a high risk accident, in 2013 there are 57 CC operation accidents at PT X. Accident high PC operations require companies to prevent and reduce the risk of accidents at the company, according Act No. 1 Year 1970 Article 3, paragraph 1. Reduce and prevent the risk of workplace accidents by conducting a risk assessment. This study aims to assess the risk.The design of this study was observational with crossectional approach. The main aim of this study was to assessed of risk on CC operate in PT X Surabaya. The subject in this study were safety officer maintenance, technician and CC operator. The object in this study was CC unit. The data were collected by means of observation and interview, while the secondary data from the operation of the CC documents related accidents. The data obtained were analyzed descriptively by tabulations and narration which of compared with the standard ISO 31000: 2009 as well as the existing theories. The results of this study show that there were 4 process of work that has 9 cause danger of accident, 2 causes of accident with the high risk, 5 moderate risk and 2 low risk. Risk control that has done are engineering, administrative, and PPE. From the result of this study, it is recommended that the company provide to implement the work according to SOP, conduct load test and check the condition of the lift on the entire CC, check and repair functions anemometer and sirens on CC, give emergency drill evenly for workers.Keywords: accident risk assessment, Container Crane (CC)